A taxonomic study of the genus Amusurgus Brunner von Wattenwyl from China (Orthoptera, Gryllidae, Trigonidiinae) - He, Zhuqing; Li, Kai; Fang, Yan; Liu, Xianwei (Zootaxa, 2010)
A taxonomic study of the genus Amusurgus Brunner von Wattenwyl, 1893 from China is presented. The genus is divided into three subgenera by the difference of tympana. Five species are described with two new species, one new combination, one resurrected name and one new synonymy. Keys to subgenera and species from China are given.